Provenance Analysis Based On Petrographic Samples On EXIA-1 Well, Banggai Basin, East Sulawesi, Indonesia - Setyawan, Reddy; Aribowo, Yoga; Kurniasih, Anis; Fahrudin; Ali, Rinal Khaidar; Najib; Ferdy; Wijaya, Ennur Kusuma; Qadaryati, Nurakhmi; Khorniawan, Wahyu Budhi; Dalimunte, Hasnan Luthfi; Ringga, Anita Galih (UIR PRESS, 2024)
The structure of Exia is composed of Miocene built-up carbonates formed by shear faults. The buildup carbonate feature in the Exia prospect can be seen from the high elevation surrounded by lows with an NNE-SSW and NE-SW trending. The MA-1, SE-1, MI-1 wells are several wells in the Tiaka and Senoro Fields which are proven to have large gas reserves. Tiaka Field is located to the west of the Exia Well, while Senoro Field is to the northeast. The study used primary data from the Exia-1 well in the form of cutting samples. The wet and dry cutting samples were further processed into thin section. This thin section is then carried out for petrographic, XRD, and SEM analysis. Tomori Formation starts from the deeper environment FZ1 upwards to the shallower FZ5 –FZ6 (reef) with open marine and restricted areas. The allochem that composes the limestone at The Matindok Formation consists of red algae fragments and benthic forams which indicate the facies zone of formation in FZ 4 (slope). In the upper Mantawa Formation, it is still quite clear the presence of large forams indicating a reef association environment (FZ5-FZ6), but the presence of a large number of planktonic forams indicates a deeper depositional environment / slope, so it is possible that large forams were transported from a shallower environment. The Kintom Formation have rock provenance ranging from continental blocks in the interior of the craton to a recycled orogeny section of recycled quartz zone.